Design and fabrication of multi purpose ladder - Muhammad Qaidir, Abdillah (2008)
The idea to design and fabricate a multi purpose ladder is come from a supervisor that gives a task and a title for this project. To design and fabricate this multi purpose ladder, the existing product in market must be compared first to know the latest designs that have been created. The information about current design for multi purpose ladder must be search or find from magazine, newspaper, catalog or internet. From all the information, idea to design and fabricate can be created. It includes many things about multi purpose ladder that want to be design such as portable and foldable. This because, some of the current ladder is heavy, uses a lot ofspace to stored and not stable. The whole of the project involve various methods like the concept design, the designing and also the fabrication process. After the fabrication process is completed, the multi purpose ladder is tested to make sure the product is functional and achieves the objectives successfully. Overall, this project can bring a motivation and experience, train to work under the pressure, apply knowledge that have been learned and soft skill ability like time management, planning the task, and negotiation skill to make sure this project goes smooth as plan and done at correct time.